Temperature variations in pharmaceutical storage facilities and knowledge, attitudes, and practices of personnel on proper storage conditions for medicines in southern Malawi - Khuluza, Felix; Chiumia, Francis Kachidza; Nyirongo, Happy Magwaza; Kateka, Chifundo; Hosea, Raphael Abbuh; Mkwate, Westonie (Frontiers in Public Health, 2023)
Objective We assessed the temperature variations in pharmacies and medicine storage areas in southern Malawi and conducted a knowledge, attitude and practices survey for personnel who manage medicine stores in various health facilities. Methods This was a longitudinal study design that used installed Tempmate® thermometers in 27 selected health facilities to record temperatures every 15 min for a period of 9 months. In addition, a questionnaire was used to assess the knowledge, attitude, and practices regarding good pharmaceutical storage. Observations were also made on the storage structures of the facilities and compared with the mean kinetic temperature. Results Storage temperature ranged from 13.8°C to 42°C with mean kinetic temperature (MKT) being 25.3°C (95% CI 24.4–26.2°C). Mean temperature for public facilities was lower (23.8°C) than the faith-based facilities (25.2°C) and private facilities (26.6°C). In terms of level of health care, lower temperatures were recorded in facilities offering tertiary level of care as compared to secondary and primary care facilities, p < 0.001. For the type of storage facilities, storage-in-a-box unit (SIAB) presented lower temperatures than ordinary storage areas (non-SIAB), p < 0.001. Majority of health workers (69%) had good knowledge on proper storage conditions. Air conditioners and thermometers were available in 88.4 and 76.9% of the facilities, respectively. However, few facilities utilized the air conditioners due to electricity problems. About 46.15% of the participants were able to correctly record temperatures (at least twice a day) for the storage facilities, 23.07% did not properly record while 30.77% of the personnel did not keep temperature records at all. Limited storage space was among the challenges that facilities encounter to maintain proper storage conditions. Conclusion Despite having the necessary knowledge on proper storage conditions, the pharmacy personnel failed to adhere to good pharmaceutical storage practices due to resource limitations. There is a need for stakeholder interventions such as increasing budget allocation to address the challenges faced by the health facilities.